Prognostic Impact of Early Recovering Acute Kidney Injury Following Liver Transplantation: A Multicenter Retrospective Study. Issue 4 (23rd June 2021) - Dewitte, Antoine; Defaye, Mylène; Dahmi, Anissa; Ouattara, Alexandre; Joannes-Boyau, Olivier; Chermak, Faiza; Chiche, Laurence; Laurent, Christophe; Battelier, Mathieu; Sigaut, Stéphanie; Khoy-Ear, Linda; Grigoresco, Bénédicte; et al.
Abstract : Background: Acute kidney injury (AKI) is a common complication after liver transplantation (LT), but the specific impact of rapidly resolving AKI is not elucidated. This study investigates the factors associated with early recovery from AKI and its association with post-LT outcomes. Methods: Retrospective analysis of 441 liver transplant recipients with end-stage liver disease without pretransplant renal impairment. AKI was defined according to Kidney Disease Improving Global Outcomes criteria and early renal recovery by its disappearance within 7 d post-LT. Results: One hundred forty-six patients (32%) developed a post-LT AKI, of whom 99 (69%) recovered early and 45 (31%) did not. Factors associated with early recovery were Kidney Disease Improving Global Outcomes stage 1 (odds ratio [OR], 14.11; 95% confidence interval [CI], 5.59-40.22; P < 0.0001), minimum prothrombin time >50 % (OR, 4.50; 95% CI, 1.67-13.46; P = 0.003) and aspartate aminotransferase peak value <1000 U/L (OR, 4.07; 95% CI, 1.64-10.75; P = 0.002) within 48 h post-LT. Patients with early recovery had a renal prognosis similar to that of patients without AKI with no difference in estimated glomerular filtration rate between day 7 and 1 y. Their relative risk of developing chronic kidney disease was 0.88 (95% CI, 0.55-1.41; P = 0.6) with survival identical to patients without AKI and better than patients without early recovery ( P < 0.0001). Conclusions: Most patients with post-LT AKI recover early and have a similar renal prognosis and survival to those without post-LT AKI. Factors associated with early renal recovery are related to the stage of AKI, the extent of liver injury, and the early graft function. Patients at risk of not recovering may benefit the most from perioperative protective strategies, particularly those aimed at minimizing the adverse effects of calcineurin inhibitors.